Biofortified yellow cassava and vitamin A status of Kenyan children: a randomized controlled trial - Talsma, Elise F.; Brouwer, Inge D.; Verhoef, H.; Mbera, G.N.; Nwangi, A.M.; Demir, Ayse Y.; Maziya-Dixon, B.B.; Boy, Erick; Zimmermann, Michael B.; Melse-Boonstra, Alida (Elsevier, 2016)
Background: Whereas conventional white cassava roots are devoid of provitamin A, biofortified yellow varieties are naturally rich in b-carotene, the primary provitamin A carotenoid. Objective: We assessed the effect of consuming yellow cassava on serum retinol concentration in Kenyan schoolchildren with marginal vitamin A status. Design: We randomly allocated 342 children aged 5–13 y to receive daily, 6 d/wk, for 18.5 wk 1) white cassava and placebo supplement (control group), 2) provitamin A–rich cassava (mean content: 1460 mg b-carotene/d) and placebo supplement (yellow cassava group), and 3) white cassava and b-carotene supplement (1053 mg/d; b-carotene supplement group). The primary outcome was serum retinol concentration; prespecified secondary outcomes were hemoglobin concentration and serum concentrations of b-carotene, retinol-binding protein, and prealbumin. Groups were compared by using ANCOVA, adjusting for inflammation, baseline serum concentrations of retinol and b-carotene, and stratified design. Results: The baseline prevalence of serum retinol concentration, 0.7 mmol/L and inflammation was 27% and 24%, respectively. For children in the control, yellow cassava, and b-carotene supplement groups, the mean daily intake of cassava was 378, 371, and 378 g, respectively, and the total daily supply of provitamin A and vitamin A from diet and supplements was equivalent to 22, 220, and 175 mg retinol, respectively. Both yellow cassava and b-carotene supplementation increased serum retinol concentration by 0.04 mmol/L (95% CI: 0.00, 0.07 mmol/L); correspondingly, serum b-carotene concentration increased by 524% (448%, 608%) and 166% (134%, 202%). We found no effect on hemoglobin concentration or serum concentrations of retinol-binding protein and prealbumin. Conclusions: In our study population, consumption of yellow cassava led to modest gains in serum retinol concentration and a large increase in b-carotene concentration. It can be an efficacious, new approach to improve vitamin A status. This study was registered with clinicaltrials.gov as NCT01614483.